Institutional Barriers and Social Work Strategies in the Rehabilitation of Trafficked Persons: The Case of Albania - Bicoku, Alisa; Belshaku, Sabina (European Journal of Social Science Education and Research, 2026)
Human trafficking persists as a significant human rights challenge in Albania, demanding robust and sustainable rehabilitation responses. This study investigates the institutional mechanisms and social work practices shaping the rehabilitation of trafficked persons in this Balkan transitional context. Employing a qualitative-dominant mixed-methods design, the research combines systematic document analysis of legal and policy frameworks with semi-structured interviews (n=25) involving social workers, NGO practitioners, law enforcement, and policymakers. The findings reveal a critical gap between Albania's well-developed legal framework, including its National Referral Mechanism, and the practical realities of long-term reintegration. While emergency protection services are relatively effective, sustainable recovery is undermined by fragmented inter-agency coordination at the local level, inequitable geographic access to services, and precarious short-term funding models. Social workers are identified as pivotal actors who navigate these systemic gaps, yet their efficacy is constrained by high caseloads and inconsistent professional development. The study argues for institutionalizing trauma-informed care and integrating anti-trafficking efforts with broader social inclusion policies to foster genuine, long-term recovery and prevent re-trafficking.
Keywords: victim reintegration; trauma-informed practice; social welfare services; institutional coordination; transitional justice; human trafficking